PENGARUH PENGGUNAAN MEDIA KARTU SUKU KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK BERKESULITAN MEMBACA KELAS V DI SDN TALUN 1 MANCAK - Ajeng Sawytri, Berliana; Yudha Pratama, Toni; Asmiati, Neti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the problem of childrenwith reading difficulties who still experience obstaclesin early reading skills, including reading letters,syllables, and words, which affects the reading abilityand learning process in the classroom,. The purposeof this study is to determine the effect of using syllablecard media on early reading skills in children withreading difficulties,. This research was conducted on afifth-grade student with reading difficulties at SDNTalun 1 Mancak with the initials SH,. The researchmethod used is quantitative with a Single SubjectResearch (SSR) approach using an A-B-A design,.Data collection techniques were carried out throughinitial reading ability tests and observations during theintervention process,. Data were analyzed using visualanalysis within and between conditions. This is shownby the increase in the mean level from the baseline-1(A1) phase of 32%, the intervention (B) phase of88.5%, and the baseline-2 (A2) phase of 88%,,. Theresults of the study show that the use of syllable cardmedia has a positive effect on improving children'searly reading skills,. By using syllable card media, thesubject gradually experienced an increase in the abilityto read letters, syllables, and words more accuratelyand fluently,. Thus, this research can answer thehypothesis that the use of syllable card media canimprove the subject's initial reading skills.